Occupational medicine in Germany – with special focus on occupational cancer. Review and critical discussion / La medicina del lavoro in Germania, con particolare riguardo ai tumori professionali - Ochmann, U.; Nowak, D.; Heinzow, B. (European Journal of Oncology and Environmental Health, 2012)
Aim. Description of the legal framework of occupational medicine in Germany with emphasis on the reported and notified cases of occupational cancer. Methods. Description and review of the current legislation and statistical data from the German: Documentation of the Occupational Disease Occurrence. Results. The dual German occupational health system is rather complex with different responsibilities of several stakeholders involved. Due to changes of legislation the number of notified occupational diseases shows some variation over the past. In 2010, 73.425 cases have been notified based on a suspicion on the existence of an occupational disease, of which a quarter has been accepted and 10% has been compensated. Occupational cancers are mainly related to asbestos (75%), followed by exposure to ionizing radiation (10%) and aromatic amines (5%). The incidence of some occupational cancers is still on the rise; most importantly the peak for mesothelioma incidence has not been reached yet. Conclusions. Recognition of an occupational disease and receiving compensation is confined to listed diseases and stringent criteria of exposure and diagnostic parameters. In other cases it allows few workers actually to receive compensation. Mainly for asbestos related occupational lung and larynx-cancers with long latency periods under reporting must be assumed. Comparison with other European countries indicates heterogeneous recognition procedures, with considerable differences in accepted cases between countries. A harmonized thorough European documentation of occupational diseases and occupational cancers should be pursued in the interest of occupational justice and primary prevention.La medicina del lavoro in Germania, con particolare riguardo ai tumori professionaliFinalità. Descrizione della situazione legale della medicina occupazionale con particolare enfasi sui casi segnalati e notificati come tumori professionali in Germania. Metodi. Descrizione e revisione dell’attuale legislazione e dei dati statistici provenienti dal tedesco: Documentazione sulla Insorgenza delle Malattie Professionali. Risultati. Il sistema sanitario occupazionale tedesco, di tipo duale, è piuttosto complesso, con differenti responsabilità di molte parti interessate. A causa dei cambiamenti legislativi, il numero delle malattie professionali notificate mostra alcune variazioni rispetto al passato. Nel 2009, sono stati notificati 70.100 casi sulla base di un sospetto a proposito dell’esistenza di una malattia professionale. Un quarto del totale è stato riconosciuto e il 10% è stato indennizzato. I tumori professionali vengono correlati soprattutto all’amianto (75%), seguiti da quelli dovuti all’esposizione e alle radiazioni ionizzanti (10%) e ad amine aromatiche (5%). L’incidenza di alcuni tumori professionali è ancora in aumento, in particolare il picco di incidenza del mesotelioma non è stato ancora raggiunto. Conclusioni. Per poter confrontare i dati dei diversi paesi è necessario essere consapevoli che esistono delle differenze metodologiche tra i paesi stessi per quanto riguarda le procedure legali e i codici così come la fonte e la qualità dei dati. Le limitazioni del sistema di segnalazione tedesco che sono state identificate richiedono un intervento. Nell’interesse della giustizia professionale e della prevenzione primaria, sarebbe necessario raggiungere una armonizzazione attraverso una documentazione europea sulle malattie e sui tumori professionali